2014
DOI: 10.1007/s40262-014-0180-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacokinetics and Pharmacodynamics of the Novel SGLT2 Inhibitor Ipragliflozin

Abstract: Ipragliflozin (Suglat(®)) is a potent and selective inhibitor of sodium-glucose cotransporter-2 that was recently launched in Japan. Its mechanism of action involves the suppression of glucose re-absorption in the kidney proximal tubules, causing excretion of glucose in the urine. The aim of this review is to provide a comprehensive overview of currently available pharmacokinetic and pharmacodynamic data on ipragliflozin, including studies in healthy subjects, patients with type 2 diabetes mellitus and special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 34 publications
1
31
1
Order By: Relevance
“…The clinical pharmacokinetics and pharmacodynamics of the novel SGLT2i ipragliflozin, which has gained approval for clinical use in T2D in Japan, have been reviewed [68] . To investigate the effect of ipragliflozin on the pharmacokinetics of sitagliptin and vice versa, ipragliflozin 150 mg and sitagliptin 100 mg were administered alone or in combination in two cohorts of 32 healthy subjects [69] .…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…The clinical pharmacokinetics and pharmacodynamics of the novel SGLT2i ipragliflozin, which has gained approval for clinical use in T2D in Japan, have been reviewed [68] . To investigate the effect of ipragliflozin on the pharmacokinetics of sitagliptin and vice versa, ipragliflozin 150 mg and sitagliptin 100 mg were administered alone or in combination in two cohorts of 32 healthy subjects [69] .…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Therefore, further decreases in nocturnal glucose levels are not thought to be caused due to intake of tofogliflozin. In contrast, ipragliflozin is thought to pose a risk of further decrease in nocturnal glucose levels, in combination with insulin because ipragliflozin has a long half-life, and therefore acts firmly during the nighttime [22]. We think that occurrence of nocturnal and overall hypoglycemia was significantly lower in patients on tofogliflozin, than in those on ipragliflozin because of the above-mentioned difference between tofogliflozin and ipragliflozin.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, this supports the hypothesis that the effect of tofogliflozin taken in the morning almost disappears during the nighttime. In contrast, it has been reported that Tmax of ipragliflozin is 1.4 hours and its half-life is 15 hours [22]. Therefore, ipragliflozin affects the individual for a constant duration (steady state).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations